Dietary selenium intake, aldehyde dehydrogenase‐2 and X‐ray repair cross‐complementing 1 genetic polymorphisms, and the risk of esophageal squamous cell carcinoma - Cai, Lin; You, Nai‐Chieh Yuko; Lu, Hua; Mu, Li‐Na; Lu, Qing‐Yi; Yu, Shun‐Zhang; Le, Anh D.; Marshall, James; Heber, David; Zhang, Zuo‐Feng (Cancer, 2006)
BACKGROUND To the authors' knowledge, few studies have been conducted to date regarding dietary selenium and the potential gene‐nutrient interactions with single‐nucleotide polymorphisms (SNPs) in different pathways on the risk of esophageal cancer. METHODS The authors investigated the role of dietary selenium intake and its interplay with SNPs of the ALDH2 (glutamic acid [Glu] 487 lysine [Lys]) and the X‐ray repair cross‐complementing 1 (XRCC1) (arginine [Arg] 399 glutamine [Gln]) genes on the risk of esophageal squamous cell carcinoma (ESCC) in a population‐based, case‐control study in China. In total, 218 patients with ESCC and 415 healthy population control participants were interviewed. Dietary selenium intake was estimated from a food frequency questionnaire with 97 food items. ALDH2 and XRCC1 polymorphisms were detected with a polymerase chain reaction‐restriction fragment length polymorphism assay. RESULTS The adjusted odds ratio (OR) for the highest quintile of dietary selenium intake, compared with the lowest quintile of intake, was 0.48 (95% confidence interval [95% CI], 0.25‐0.89), with a strong dose‐response relation (P for trend, <.01). The ALDH2 Lys and XRCC1 Gln variant alleles were associated with an increased risk of ESCC with adjusted ORs of 1.91 (95% CI, 0.96‐3.80) and 1.67 (95% CI, 1.08‐2.59), respectively. An elevation of the risk for ESCC was pronounced most among carriers of ALDH2 Lys/Lys and XRCC1 399Gln/Gln or Gln/Arg who consumed a low level of dietary selenium (adjusted OR, 4.16; 95% CI, 1.14‐15.12). CONCLUSIONS To the authors' knowledge, this is the first in‐depth study to suggest that genetic susceptibility may modify the association between selenium intake and the risk of ESCC. The findings indicated that individuals with low dietary selenium intake and ALDH2 Lys/Lys and XRCC1 399Gln/Gln or Gln/Arg genotypes were associated with an increased ESCC risk, especially in the presence of exposure to tobacco and alcohol carcinogens. Cancer 2006. © 2006 American Cancer Society. The authors investigated the possibility that genetic susceptibility might modify the associations of dietary selerium intake with the risk of esophageal squamous cell carcinoma (ESCC). The results indicated that individuals with low dietary selerium intake, ALDH2 Lys/Lys and XRCC1 399Gln/Gln or Gln/Arg genotypes were associated with an increased risk of ESCC, especially in the presence of exposure to tobacco and alcohol carcinogens.